The effect of restricted exercise of sow behaviour and reproductive performance - Parry, Margaret A. (1984)
20 Large White x Landrace sows were kept throughout 4 parities on 1 of 2 exercise treatments, free (F) or restricted (R), imposed at 2 stages of the production cycle (namely gestation and farrowing/lactation), thus giving 4 treatments: FF, FR, RF and RR. During gestation, the sows were housed in cubicles - group a being tethered while group F were allowed unrestricted movement within the cubicle and dunging area. From day 110 of gestation to weaning, all sows were kept in the same farrowing house, group R in conventional crates, group F in strawed pens. Management of the sows was otherwise identical. All farrowings were monitored with regard to the duration of parturition and stillbirth rate, while various behavioural and physiological measurements were recorded as indicators of piglet viability. Observations were also made of now behaviour at various stages of the production cycle. There were significant (P< 0.001) behavioural differences in gestation with groups R and F spending 45% v. 25% of the time lying and 27% v. 42% in manipulating straw. There were also significant (P<0.001) differences in amount and type of locomotor activity with the restricted sows making more minor movements while the free sows made more pace movements. At farrowing, all sows showed increased restlessness but group a made more leg movements and exhibited significantly (P<0.01) more straining and quivering (both pre- and intrapartum) than group F, although the latter stood and nested more frequently during the farrowing process (P< 0.001). There were no significant differences between treatments during lactation. In terms of reproductive performance, the differences between treatments were non significant, but sows in pens (group F) farrowed more quickly (a mean birth interval of 21 v. 39 minutes), produced more live pigs (11.3 v. 10.5) and fewer stillborn pigs (0.5 v. 0.8) per litter, than sows in crates (group a). Group F sows also produced piglets which had been subjected to less hypoxia as evidenced by their lower (P <0-05) serum lactic acid levels at birth (140 v. 158 m.I.U./ml) although there were no significant differences between piglets of groups F and R in times taken to breathe following birth or (53 v. 45 seconds), to suckle (36 v. 32 minutes) or in plasma immunoglobulin levels at 36 hours post partum (41.5 v. 41.7 mg/ml). Neither were there any significant treatment effects on piglet growth rate and pre-weaning mortality.